COGNITIVE FUNCTIONS AND HIGH ORDER THINKING SKILLS IN MEDICAL EDUCATION - Arifin, Fransiscus (JURNAL WIDYA MEDIKA, 2025)
The improvement of cognitive functions and higher-order thinking skills (HOTS) is fundamental to the development of competent and adaptive medical professionals. As medical education evolves to meet the demands of complex healthcare systems, there is an increasing emphasis on nurturing analytical reasoning, clinical judgment, problem-solving, and metacognitive awareness among students. This review explores the integration of cognitive science principles and Bloom’s taxonomy of higher-order thinking skills. We evaluate the literature on the connections between memory, attention span, and metacognition with higher-order thinking skills such as problem-solving and creativity. We suggest that daily classroom teaching and medical curriculum design should focus on strengthening cognitive functions such as memorization and attention span, as well as promoting metacognition.